The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/cnma.202100235
|View full text |Cite
|
Sign up to set email alerts
|

Materials Development in Hybrid Zinc‐Ion Capacitors

Abstract: High‐performance energy storage devices have an exceptional role in modern applications such as green transportation, consumer electronics and electrical systems. Recently, the hybrid supercapacitor has gained great interest among researchers that adopt a combination of capacitive and battery‐type electrodes to increase the energy density without sacrificing the power performance. Different types of hybrid energy storage devices have been reported recently including lithium‐ion capacitor (LIC), sodium‐ion capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 110 publications
0
14
0
Order By: Relevance
“…The surface morphology of the prepared NCO, NMCO4, NMCO3, NMCO2, NMCO1, and MCO thin films were investigated using FE‐SEM, as shown in Figure 1A‐F. The FE‐SEM images revealed that the thin films exhibited a uniform and homogeneous NFs‐like nanostructure growth with a porous surface and sharp vertical‐edged highly porous NFs 20‐22 . Figure 1A shows the FE‐SEM images of the interconnected chain of the nanoflower‐like nanostructures of NCO thin film.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface morphology of the prepared NCO, NMCO4, NMCO3, NMCO2, NMCO1, and MCO thin films were investigated using FE‐SEM, as shown in Figure 1A‐F. The FE‐SEM images revealed that the thin films exhibited a uniform and homogeneous NFs‐like nanostructure growth with a porous surface and sharp vertical‐edged highly porous NFs 20‐22 . Figure 1A shows the FE‐SEM images of the interconnected chain of the nanoflower‐like nanostructures of NCO thin film.…”
Section: Resultsmentioning
confidence: 99%
“…The FE-SEM images revealed that the thin films exhibited a uniform and homogeneous NFs-like nanostructure growth with a porous surface and sharp vertical-edged highly porous NFs. [20][21][22] Figure 1A shows the FE-SEM images of the interconnected chain of the nanoflower-like nanostructures of NCO thin film. At high magnification (as shown in the inset of Figure 1A), the NFs with an average length and thickness of 200 to 300 and 25 to 35 nm, respectively, were interconnected to each other on a highly porous surface area.…”
Section: Surface Morphological Studiesmentioning
confidence: 99%
“…10 With these advantages, the energy storage mechanism of multivalent cations (Zn 2+ , Mg 2+ , Ca 2+ , and Al 3+ ) has been applied to multivalent-ion hybrid capacitors (MIHCs), and the latest developments and design ideas for these have been recently reviewed. [11][12][13] However, an overview from the perspective of materials with unique advantages and experimental designs remains limited. Carbon-based nanomaterials are leading candidates for next-generation energy storage devices due to their outstanding properties in MIHCs.…”
Section: Introductionmentioning
confidence: 99%
“…19 as high-performance positive electrodes. 20,21 Compared to Prussian blue analogues, the manganese oxide-and vanadium oxide-based positive electrodes offer high capacity due to their suitable tunnel/layered structure to host the Zn 2+ ions. 22 On the anode side, protecting the metallic zinc via interfacial engineering with an artificial solid electrolyte interface to regulate the dendrite-free zinc deposition or engineering a three-dimensional (3D) zinc anode with an integrated gel electrolyte to push the hydrogen evolution reaction overpotential has been reported to further improve the cycle stability and rate capability of zinc ion batteries.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The last 5 years have witnessed significant research activities on the development of aqueous zinc ion batteries with task-specific structurally modified manganese oxides, Prussian blue analogues, vanadium oxides, biphasic vanadates, etc . as high-performance positive electrodes. , Compared to Prussian blue analogues, the manganese oxide- and vanadium oxide-based positive electrodes offer high capacity due to their suitable tunnel/layered structure to host the Zn 2+ ions . On the anode side, protecting the metallic zinc via interfacial engineering with an artificial solid electrolyte interface to regulate the dendrite-free zinc deposition or engineering a three-dimensional (3D) zinc anode with an integrated gel electrolyte to push the hydrogen evolution reaction overpotential has been reported to further improve the cycle stability and rate capability of zinc ion batteries. , Nevertheless, the development of a zinc ion capacitor (ZIC) has been relatively less explored …”
Section: Introductionmentioning
confidence: 99%